The Influence of Web Design Quality, Perceived Ease of Use And Trust on Purchase Intention: A Case Study on Lazada - Yahya Setia Budi; Fitri Ayu Nofirda; Wan Laura Hardilawati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the effect of web design quality, perceived ease of use and trust on purchase intention. This research is a quantitative research. Source of data used in this study is primary data with data collection method is a questionnaire. The population in this study were all active students of the Management Study Program at Muhammadiyah University of Riau, totaling 1,116 students. Sampling used a purposive sampling method, with the criteria of active students in the Management Study Program and having made online transactions through Lazada e-commerce at least twice in the last six months with a total sample of 92 respondents. The data obtained in this study were processed using IBM Statistics SPSS 25 with 81 questionnaires. The results of the study show that web design quality, perceived ease of use and trust have a positive and significant effect on purchase intention. Keywords: Web Design Quality, Perceived Ease Of Use, Trust, Purchase Intention.